2005
DOI: 10.1149/1.1862478
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Characterizations of Electrodeposited p-Type Semiconductor Cu[sub 2]O Films

Abstract: The p-type semiconductor cuprous oxide ͑Cu 2 O͒ film has been of considerable interest as a component of solar cells and photodiodes due to its bandgap energy of 2.1 eV and high optical absorption coefficient. We prepared Cu 2 O films on a conductive substrate by electrodeposition at 318 K from an aqueous solution containing copper sulfate and lactic acid. The structural and electrical characterizations of the resulting films were examined by X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(144 citation statements)
references
References 14 publications
8
135
0
1
Order By: Relevance
“…3(a)). The resistivities obtained for films grown at 150 • C are two orders of magnitude lower than the lower bound for the resistivity of Cu 2 O films made by electrodeposition 17 and comparable to the lower values reported for sputtered films at room temperature. 14,48 The results obtained for films deposited on PEN substrates at 150 • C were of the same order as those obtained on glass.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under supporting
confidence: 64%
See 1 more Smart Citation
“…3(a)). The resistivities obtained for films grown at 150 • C are two orders of magnitude lower than the lower bound for the resistivity of Cu 2 O films made by electrodeposition 17 and comparable to the lower values reported for sputtered films at room temperature. 14,48 The results obtained for films deposited on PEN substrates at 150 • C were of the same order as those obtained on glass.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under supporting
confidence: 64%
“…13 Cu 2 O thin films can be deposited by several methods including pulsed laser deposition (PLD), 8 sputtering, 14 thermal oxidation, 15 spray pyrolysis 16 and electrochemical deposition. 17 Sputtering appears to be the most successful vacuum method for achieving high mobilities at low temperatures. Indeed, films grown at room temperature have been reported to have carrier mobilities up to 10 cm 2 V −1 s −1 18 and even higher values (∼50 cm −2 V −1 s −1 ) have been reported at higher temperatures.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…Generally, cuprous oxide is observed to be a p-type semiconductor in the as-deposited state. This is attributed to the fact that it has a bandgap of 2.1 eV 31 and an electron affinity of 2.9eV. 32 In addition, it may be considered as a degenerate semiconductor also because of its high work function of 5.36 eV, as experimentally proved by A.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] The pH dependence of the crystal orientation during Cu 2 O electrodeposition may be ascribable to changes in the dissolved copper(II)-lactate complexes. 6,15,16 Unfortunately, to the best of our knowledge, there are no available thermodynamic data for these copper(II)-lactate complexes under these alkaline conditions, especially for such concentrated solutions. Two previous reports have indicated the presence of dissolved copper(II)-lactate complexes in such concentrated alkaline solutions; Leopold et al assumed In this study, we identified the copper(II)-lactate complexes in Cu 2 O electrodeposition baths.…”
mentioning
confidence: 99%
“…[13][14][15][16] The crystal orientation of the electrodeposited Cu 2 O is pH dependent; i.e. it is <100> at pH values of 9.0 and 9.5, and <111> at pH values of 12.0 and 12.5.…”
mentioning
confidence: 99%